Antiplatelet therapy following transcatheter aortic valve implantation. Issue 14 (6th May 2015) - Hassell, Mariëlla E C J; Hildick-Smith, David; Durand, Eric; Kikkert, Wouter J; Wiegerinck, Esther M A; Stabile, Eugenio; Ussia, Gian Paolo; Sharma, Sumeet; Baan, Jan; Eltchaninoff, Hélène; Rubino, Paolo; Barbanti, Marco; et al.
Abstract : Objective: There is limited evidence to support decision making on antiplatelet therapy following transcatheter aortic valve implantation (TAVI). Our aim was to assess the efficacy and safety of aspirin-only (ASA) versus dual antiplatelet therapy (DAPT) following TAVI. Methods: We performed a systematic review and pooled analysis of individual patient data from 672 participants comparing single versus DAPT following TAVI. Primary endpoint was defined as the composite of net adverse clinical and cerebral events (NACE) at 1 month, including all-cause mortality, acute coronary syndrome (ACS), stroke, life-threatening and major bleeding. Results: At 30 days a NACE rate of 13% was observed in the ASA-only and in 15% of the DAPT group (OR 0.83, 95% CI 0.48 to 1.43, p=0.50). A tendency towards less life-threatening and major bleeding was observed in patients treated with ASA (OR 0.56, 95% CI 0.28 to 1.11, p=0.09). Also, ASA was not associated with an increased all-cause mortality (OR 0.91, 95% CI 0.36 to 2.27, p=0.83), ACS (OR 0.5, 95% CI 0.05 to 5.51, p=0.57) or stroke (OR 1.21; 95% CI 0.36 to 4.03, p=0.75). Conclusions: No difference in 30-day NACE rate was observed between ASA-only or DAPT following TAVI. Moreover, a trend towards less life-threatening and major bleeding was observed in favour of ASA. Consequently the additive value of clopidogrel warrants further investigation.